Mapeamento do estado nutricional do mamoeiro - Jesus, Mariana Lima de (2016)
Geostatistics is used in study of spatial variability based on the estimation and identification of the interrelationships of the attributes studied, in space and time, allowing the optimization of sampling grid considering the spatial dependence between